Seminar Digital Penguatan Sumber Daya Manusia Pendidikan Tinggi Menuju Indonesia Emas 2045 - Hadi Prayitno; Ahmad Bahrawi; Faoyan Agus Furyanto; Ikhwanul Qiram (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
Indonesia Gold 2045 requires higher education institutions to strengthen academic human resources who are adaptive, innovative, and globally competitive. However, lecturers and education personnel still need practical understanding of competency development, learning innovation, and cross-sector collaboration strategies. This community service program aimed to strengthen participants' literacy on competitive human resource development through a national digital seminar. The activity was conducted online via Zoom on 12 April 2025 using a participatory approach consisting of preparation, educational material delivery, interactive discussion, monitoring, evaluation, and follow-up publication. The participants were 93 lecturers and education personnel from higher education institutions in Indonesia. Evaluation was conducted using a Likert-scale questionnaire through Google Forms and analysed descriptively. The results showed that the activity was well received: 66.3% of participants were lecturers and 33.7% were education personnel; the average scores for material benefit, material relevance, and media suitability were 3.71; the knowledge and applicable skill improvement score reached 3.85; and the speaker's delivery score also reached 3.85 on a 1-4 scale. The findings indicate that digital community service seminars can improve practical awareness, academic networking, and readiness to develop competitive human resources. The program output includes a data-based evaluation report, documentation of implementation, and recommendations for regular follow-up activities, including deeper discussion of Artificial Intelligence for human resource development.